Design of Material Composition and Technology Verification for Composite Front End Cabs - Rusnakova, Sona; Fojtl, Ladislav; Zaludek, Milan; Rusnak, Vladimir (Manufacturing Technology Journal, 2014)
Presented research paper is focused on the development of train front end cab, specifically on choice of material composition and production technology. Experimental part deals with a selection of the most appropriate multiaxial fabric based on its saturation by resin and type of polyester resin most suitable for low-pressure vacuum infusion. This technology is chosen with respect to dimensions of the part, resin savings (compared to hand lay-up technology) and also production cost of the cab. Prepared samples are evaluated regarding to the progress of production technology, part face quality (voids, dry spots, and delamination) and technological properties. As a result, optimal material composition for front end cab production is chosen and fabrication of prototype cab is conducted.
Keywords: Train Cab; Vacuum Infusion; Fiberglass Composite; Multiaxial Fabric; Polyeste r Resin